Hubungan Kelengkapan Imunisasi Dasar dengan Tumbuh Kembang Anak Usia 12-36 Bulan di Puskesmas Winong I Kabupaten Pati - Tri Kartika Setyarini; Lita Purwira Mikasyanti; Gharini Sumbaga Narhadina; Oky Rahma Prihandani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: The stunting prevalence in Indonesia has been recorded at 21.6%, with the prevalence of children suffering from malnutrition at 7.1%. There are still approximately 5-10% of children experiencing developmental delays. Chronic and recurrent infections in children can affect growth and development due to nutrient absorption disorders. Children's immunity to diseases can be improved through immunization. This research seeks to explore the correlation between the completeness of basic immunization and the growth and development of children aged 12-36 months at Puskesmas Winong I, Pati Regency. Methods: This study employs a quantitative approach with a retrospective cohort design. All children aged 12-36 months at Puskesmas Winong I were included as the study population, with samples selected through purposive sampling based on inclusion and exclusion criteria. Data were analyzed using the Chi-Square test and Fisher’s Exact test. Results: Out of 83 children, 43 received complete immunization, while 40 did not receive basic immunization. The percentage of children with normal growth was 79,5%, while those with abnormal growth was 20,5%. 92.8% of the children exhibited appropriate development, while those with inappropriate development was 7.2%. The analysis results indicate that the completeness of basic immunization is associated with child growth, with a p-value of 0.001 < 0.05 and an RR of 1.600 (95% CI: 1.259-2.034). Meanwhile, in terms of child development, a p-value of 0.01 < 0.05 with an RR of 1.176 (95% CI: 1.033-1.340) was obtained, indicating an association between basic immunization completeness and child development. Conclusion: The completeness of basic immunization is associated with the growth and development of children aged 12-36 months at the Winong I Community Health Center, Pati Regency.